Fixit [large type] - Ide, Joe (Ide, Joe. IQ novel, 2023)
"Isaiah Quintabe is up in a hospital bed, recovering from injuries sustained in his last case. As he recovers, five hundred miles from East Long Beach, he's unaware that Grace has been abducted by professional hitman Skip Hanson. Skip is savage and psychotic, determined to punish Isaiah for sending him to prison and destroying his life. Now, Isaiah and his sometimes partner, ex-hustler Juanell Dodson, must track scant clues through L.A.'s perilous landscape as Grace's predicament grows more uncertain. As the desperate hunt winds on, Isaiah fears that even if he can bring Grace home alive, things between them will never be the same"--